"Flash blending" development finance: how to make aid donor–private sector partnerships help meet the SDGs. Issue 7 (3rd October 2021) - Cohen, Marc J.; Godfrey, Claire; Jeune, Hilary; Kindornay, Shannon
ABSTRACT: Aid donors, development advocates, and finance experts increasingly look to the private sector to fill the estimated 2.5 trillion annual Sustainable Development Goals financing gap, an amount likely to increase due to effects of COVID-19. Donors use a variety of partnerships with the private sector to realise development objectives. We use the term donor–private partnerships (DPPs) to describe the broad range of arrangements between donors and private–sector actors. Using ODA to leverage private finance, innovation testing, or service delivery, modalities include blended finance, de-risking instruments, public–private partnerships, and more. Does the reality match donors' enthusiastic rhetoric? There are success stories but civil society actors and others question whether private sector engagement in development reduces poverty and inequality, advances gender justice, and achieves environmental sustainability. There may be trade-offs between development and profit making. We present our research based on frameworks we developed to categorise and assess DPPs. We applied these to 20 partnerships involving nine donors and found that donors fail to sufficiently integrate development, human rights, and environmental standards. They inconsistently implement due diligence and risk management requirements, and impact assessments are inadequate. Our frameworks offer practitioners and academics valuable tools to examine how DPPs can advance sustainable development.